Pattern of Congenital Anomalies in Pediatric Patients at dr. Doris Sylvanus General Regional Hospital: A One-Year Retrospective Study - Rayma Hayati; Yhohan Thaihutu (The International Journal of Medical Science and Health Research, 2025)
Background : Congenital anomalies (CA) require early treatment and impair pediatric care. Knowing demographic group incidence, classification, and distribution of inherent anomalies helps treatment and resource allocation. Aims : This study examines forms and demographics of CA in children treated at dr. Doris Sylvanus Regional Hospital for a year. Methods : A retrospective study was carried out by analyzing 320 patient files between July 2023-June 2024 at dr. Doris Sylvanus General Regional Hospital. The classification system ICD-10 was used for the evaluation of frequency, gender, and geographical distribution of CA. Results : The obtained analysis revealed a higher incidence of CA in males than in females: 208 (65%) and 112 (35%), respectively. There were 72 (22.5%) cases of CA in the genital organs, the highest number found, followed by the circulatory system with 67 (20.9%) and digestive system with 44 (13.75%) cases. Most patients are coming from the city of Palangka Raya, where 197 cases were reported (61.56%), followed by Gunung Mas with 28 cases (8.75%) and East Kotawaringin with 20 cases (6.25%). Several diagnoses are often made, such as Down syndrome, Hirschsprung disease, and congenital heart malformation. Discussion : The findings provide evidence of the need for specific health interventions in regions that seem to have higher rates of CA, including the city of Palangka Raya. The gender bias found in this research is supported, and its presence is to be further deeply probed. Timely detection of focused therapeutic management is critical in getting better outcomes among children born with CA. Conclusion : The analysis indicated a significant prevalence of abnormalities in the genital and circulatory systems, highlighting the urgent requirement for specialized health services to address these issues at an earlier stage in life. The prevalence of congenital abnormalities is greater in males and in urban regions like Palangka Raya, where access to health services is more prevalent.  This disparity in access to health services between urban and rural areas is prevalent globally and significantly hinders the attainment of universal health coverage across all regions of Indonesia.  This study's findings align with a broader investigation in the area, indicating that disparities in access to health services and health outcomes are influenced by socioeconomic, geographic, and demographic factors.